Adsorptive Removal of Phosphate From Wastewater Using Ethiopian Rift Pumice: Batch Experiment. Issue 13 (November 2020) - Fetene, Yohannis; Addis, Taffere
Phosphorous from municipal and industrial wastewater is the main cause of eutrophication of rivers and lakes, because effluent quality from conventional secondary wastewater treatment plants does not meet the discharge standard that demands further treatment. Therefore, we investigated pumice as a potential low-cost adsorbent for the tertiary treatment of phosphate from municipal wastewater. The phosphate adsorption process reached equilibrium after 60 minutes contact time and achieved a removal efficiency of 94.4% ± 0.7% for an adsorbent dose of 10 g/L in 3 mg/L phosphate solution. The highest phosphate removal was recorded at pH 7. The experimental data best fitted with the Redlich-Peterson isotherm and the pseudo-second-order kinetic models. The coexisting anions decreased phosphate adsorption in the order of mixture >SO4 2–  > HCO3 −  > NO3 −  > Cl −  > CO3 − . Pumice removed 95% ± 0.2% of phosphate from effluents of the secondary treatment unit of a municipal wastewater treatment plant. Furthermore, effective regeneration of saturated pumice was possible with a 0.2 M NaOH solution. Therefore, pumice could be a technically workable low-cost reusable adsorbent for phosphate removal from wastewater as a tertiary treatment to curb eutrophication of surface waters. However, further column adsorption study is recommended for a continuous flow system to optimize process design variables and scale up for field applications.